2015
DOI: 10.1039/c5ja00308c
|View full text |Cite
|
Sign up to set email alerts
|

Removal of spectral interferences on noble metal elements using MS/MS reaction cell mode of a triple quadrupole ICP-MS

Abstract: Complex spectral interference on eight noble metal elements was removed by using a MS/MS reaction cell of triple quadrupole ICP-MS using NH3 cell gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 26 publications
0
39
1
1
Order By: Relevance
“…On the other hand, while the utilization of ICPMS/MS eliminates polyatomic interferences such as 40 Ar 38 Ar 1 H + and 40 Ar 40 Ar 1 H + , which can also interfere with the bromine isotopes at m / z 79 and especially 81, the observed LODs in the present study are comparable with those previously reported using single-quadrupole ICPMS (e.g., 0.7–1.0 μg L –1 for bromo-, dibromo-, and tribromoacetic acids 50 and 0.8 μg L –1 for bromate, 62 based on the 79 Br isotope). Although we attempted to find a compromise in the optimum ICPMS/MS instrumental parameters for the simultaneous chlorine and bromine detection, the generally higher drop in sensitivity for bromine (14%) compared with chlorine (45%) in the hydrogen cell gas mode relative to the no gas mode 63 would be expected to offset at least some of the benefit of the decreased background achieved by the elimination of the 40 Ar 38 Ar 1 H + polyatomic interference in ICPMS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, while the utilization of ICPMS/MS eliminates polyatomic interferences such as 40 Ar 38 Ar 1 H + and 40 Ar 40 Ar 1 H + , which can also interfere with the bromine isotopes at m / z 79 and especially 81, the observed LODs in the present study are comparable with those previously reported using single-quadrupole ICPMS (e.g., 0.7–1.0 μg L –1 for bromo-, dibromo-, and tribromoacetic acids 50 and 0.8 μg L –1 for bromate, 62 based on the 79 Br isotope). Although we attempted to find a compromise in the optimum ICPMS/MS instrumental parameters for the simultaneous chlorine and bromine detection, the generally higher drop in sensitivity for bromine (14%) compared with chlorine (45%) in the hydrogen cell gas mode relative to the no gas mode 63 would be expected to offset at least some of the benefit of the decreased background achieved by the elimination of the 40 Ar 38 Ar 1 H + polyatomic interference in ICPMS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…It was expected that spectral interferences in determination of Pd, Pt and Rh mass fractions could be significantly decreased using collision/reaction cell technology together with MS/MS measurement (Agilent 8800 ICP‐MS). Previously, a study with matrix‐free standard solutions containing interfering elements demonstrated the usefulness of ammonia as a reaction gas in ICP‐MS/MS determination of noble metals (Sugiyama and Shikamori ). Furthermore, ICP‐MS/MS has been used to remove interferences in the determinations of noble metals in geological reference materials (Bokhari et al .…”
Section: Resultsmentioning
confidence: 99%
“…With mass-shift measurement (105?156), corresponding to the formation of Pd(NH 3 ) 3 + , a significant amount of unidentified interference(s) was present. To the contrary, Sugiyama and Shikamori (2015) reported that on-mass determination of Pd mass fractions was possible at m/z 105. However, the higher Pd concentration levels allowed the use of a higher NH 3 gas flow rate (7 ml min -1 ) in the elimination of interferences.…”
Section: Selection Of the Gas Modes For Icp-ms/ms Measurementsmentioning
confidence: 99%
“…Some noteworthy examples of applications using triple quadrupole ICP‐MS hardware are as follows: Bolea‐Fernandez et al . (), who determined ultra trace mass fractions of As and Se using methyl fluoride (a mixture of 10% CH 3 F and 90% He) as a reaction gas. Sugiyama and Shikamori (), who removed polyatomic ion interferences on trace abundances of Ru, Rh, Pd, Ag, Os, Ir, Pt and Au, with highly reactive ammonia (NH 3 ) gas. Bolea‐Fernandez et al . (), who removed the isobaric overlap of 87 Sr on 87 Rb for Sr isotope determination in solid samples by LA; using CH 3 F/He (10% CH 3 F in He), Sr + ions are converted into corresponding SrF + reaction product ions, while Rb + ions show no reactivity towards this gas mixture. Virgilio et al .…”
Section: Advances In Plasma Source Mass Spectrometry and Laser Ablatimentioning
confidence: 99%
“…• Sugiyama and Shikamori (2015), who removed polyatomic ion interferences on trace abundances of Ru, Rh, Pd, Ag, Os, Ir, Pt and Au, with highly reactive ammonia (NH 3 ) gas.…”
Section: Hardware Development For Icp-msmentioning
confidence: 99%